Kenaf-based activated carbon: A sustainable solution for high-performance aqueous symmetric supercapacitors - Thilageshwaran, Subramaniam; M N M, Ansari; Syam G, Krishnan *; Mohammad, Khalid * (Elsevier, 2024)
This study presents an innovative method for synthesizing activated carbon with an exceptionally high surface area (3359 m2 g-1) using kenaf fiber-based biochar through chemical activation. The achieved specific surface area surpasses activated carbon derived from other reported fiber-based precursors. The resulting activated carbon was investigated as electrodes for supercapacitors, revealing a remarkable maximum capacitance of 312 F g-1 at a current density of 0.5 A g-1. An aqueous symmetric supercapacitor employing these high-surface-area electrodes exhibited an outstanding energy density of 18.9 Wh kg-1 at a power density of 250 W kg-1. Notably, the supercapacitor retained exceptional capacitance, maintaining 93% of its initial capacitance even after 5000 charge-discharge cycles.